Depressive symptoms among older adults: The impact of early and later life circumstances and marital status - TIMONEN, VIRPI (My University, 2013)
Objective: This article contributes to the literature on depression and the life course by examining the impact of both early and later life circumstances on depressive symptoms among men and women aged 65 and over in Ireland. Method: Data are from the first wave of The Irish Longitudinal Study on Ageing (TILDA), a nationally representative sample of 8,504 community-dwelling adults aged 50 years and older. 3,507 respondents aged 65 years and over were included in the analysis. Multinomial logistic regression was used to examine the childhood and early adult life circumstances associated with marital status. A series of nested models were estimated to evaluate which childhood and adulthood circumstances are associated with depressive symptoms. Models were estimated separately for men and women. Results: Ill health in childhood and in later life has a strong and direct effect on depression in later life for both men and women. Other early stressors are mediated by later circumstances. Marital status is a significant independent predictor of depression in later life. Later life circumstances mediate between some marital statuses and depressive symptoms. When later life circumstances are included, widowhood and, for men, divorce, are directly associated with depression, but singlehood is not. Income in later life is strongly associated with depressive symptoms for women. Conclusion: Both early and later life circumstances affect late-life depressive symptoms. Our findings indicate that previous studies which did not consider both may have underestimated or overestimated the effect of marital status, education, current health and education on depressive symptoms.
PUBLISHED
DOI:10.1080/13607863.2012.747078
Keywords: depression; life course; gender; marital status; childhood; Ageing; Inclusive Society